Optimalisasi Hak Guru dalam Meningkatkan Mutu Lulusan Madrasah Aliyah di Bengkulu - Reko Ramadani; Liberta putra baladewa; Muhammad Warobi; Ardian Pratama; M Rexsy Sahnaki (Yayasan Darussalam Bengkulu, 2025)
The purpose of this research, in addition to mapping and describing the optimization of teacher rights in improving the quality of graduates of Madrasah Aliyah in Bengkulu, is also a reference regarding the importance of optimizing teacher rights in improving the quality of graduates of Madrasah Aliyah in Bengkulu starting from increasing the optimization of the rights that must be given to teachers. The approach used in this writing is to use a descriptive qualitative method approach. Sources of information in this study, using various sources, both online media data, scientific articles and e-books related to optimizing teacher rights in improving the quality of madrasah aliyah graduates in Bengkulu. The results concluded in this study are that there is still a lack of optimization in giving teachers' rights, especially teachers who are still on honorary status. Madrasah leaders cannot take steps that are more in the form of granting honorary teacher rights, especially in terms of salary, if there is no decision from the Ministry of Education and Culture. Therefore, if the teacher's rights are not optimal, it will not be able to improve the change in the quality of graduates at the Islamic boarding school. Likewise, if the provision of teacher rights is optimal, it will easily be able to drive change so that the quality of madrasa graduates increases and excels can compete in the national realm for the future of these madrasa students. Thus it can be suggested to optimize teacher rights in order to improve the quality of aliyah madrasah graduates in Bengkulu.